Strengthening Students’ Motivation and Confidence to Achieve Learning Goals in Blended Learning Method - Athiyah S.S. Salwa; Sry Ratna Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Pandemic outbreak today has changed any sectors including education, from their normal state into the condition we never expected before. From primary to higher education, the institutions are forced to change teaching and learning models into virtual since the Government tries to stop the spread of the virus by prohibiting face-to-face classes. Online learning has come like tsunami trends as the outbreak rose. It also happened in some vocational schools where students live in the dormitory. Initially, they conducted offline classes, but they were transferred to go home as the virus spread. In one semester, they faced two models of learning, online and offline. Based on this situation, this article aims to disseminate the effectiveness of blended-learning models to improve students' motivation and confidence in speaking class by using the material to build their high-order thinking skills. The method of this study is combined between experimental and descriptive qualitative, by which the result of the study and analysis will be described in numbers and words.